GPR43 Potentiates β-Cell Function in Obesity - McNelis, Joanne C. (Diabetes, 2015)
The intestinal microbiome can regulate host energy homeostasis and the development of metabolic disease. Here we identify GPR43, a receptor for bacterially produced short-chain fatty acids (SCFAs), as a modulator of microbiota-host interaction. β-Cell expression of GPR43 and serum levels of acetate, an endogenous SCFA, are increased with a high-fat diet (HFD). HFD-fed GPR43 knockout (KO) mice develop glucose intolerance due to a defect in insulin secretion. In vitro treatment of isolated murine islets, human islets, and Min6 cells with (S)-2-(4-chlorophenyl)-3,3-dimethyl-N-(5-phenylthiazol-2-yl)butanamide (PA), a specific agonist of GPR43, increased intracellular inositol triphosphate and Ca(2+) levels, and potentiated insulin secretion in a GPR43-, Gαq-, and phospholipase C–dependent manner. In addition, KO mice fed an HFD displayed reduced β-cell mass and expression of differentiation genes, and the treatment of Min6 cells with PA increased β-cell proliferation and gene expression. Together these findings identify GPR43 as a potential target for therapeutic intervention.